2012
DOI: 10.1007/s10695-012-9740-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of reproductive performances of Gangetic leaffish, Nandus nandus through up regulation of serum Ca2+ concentration, improved morphological alteration of liver and ovary with dietary polyunsaturated fatty acids

Abstract: Incorporation of polyunsaturated fatty acids (PUFAs) as biofunctional compounds with feed is an effective way for gonadal maturation without any hazardous effects on animal health, and thus it is possible to save the vulnerable species from the danger of extinction. In the present study sperm quality, level of Ca(2+) concentration in serum, histological structure of the liver and developmental stages of ovary of an endangered fish species, Nandus nandus were investigated for the confirmation of the positive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Motin et al (2013) have found the highest GSI (%) 4.06 in September and 0.76 in December for female and male of O. pabo, respectively. Similar GSI (%) has also been reported in Colisa fasciatus and Nandus nandus (Hossen et al, 2014b;Reza et al, 2013). The values of correlation coefficient (r) were established between male GSI (%) and female GSI (%) and amongst the body weight and gonad weight and fecundity.…”
Section: Breeding Periodicity Fecundity and Spawning Performances Ofsupporting
confidence: 81%
“…Motin et al (2013) have found the highest GSI (%) 4.06 in September and 0.76 in December for female and male of O. pabo, respectively. Similar GSI (%) has also been reported in Colisa fasciatus and Nandus nandus (Hossen et al, 2014b;Reza et al, 2013). The values of correlation coefficient (r) were established between male GSI (%) and female GSI (%) and amongst the body weight and gonad weight and fecundity.…”
Section: Breeding Periodicity Fecundity and Spawning Performances Ofsupporting
confidence: 81%
“…; Reza et al. ). The intake of LC‐PUFAs from the diet is the only way for marine fish to obtain n‐3 and n‐6 essential FAs, such as EPA, DHA, and ARA, since most marine fish studied to date have shown a limited ability to synthesize these FAs from their precursors, linolenic acid and linoleic acid (Bell et al.…”
Section: Discussionmentioning
confidence: 98%
“…A positive correlation was detected between the levels of n-3 HUFA in the diet and eggs with the EPA concentration being more readily affected by dietary n-3 HUFA than DHA. Selective maintenance of DHA has also been seen during embryogenesis (Izquierdo et al, 2001) and denoting the essentiality of this fatty acid for the development of embryo and larvae (Reza et al, 2013). The percentage of morphologically normal eggs (as a parameter to determine egg viability) has been found to increase with an increase in the n-3 PUFA content in broodstock diets and an inclusion of these fatty acids as lipid droplets into the eggs (Reza et al, 2013;Hossen et al, 2014b), thus showing the importance of essential fatty acids for normal development of eggs and embryo.…”
Section: Introductionmentioning
confidence: 98%